Biodiesel Synthesis from Karanja Oil Using Transesterification Reaction - H. SONAWANE, SHIRISH; GHARAT, S.H.; DIXIT, JAYPAKASH; PATIL, KISHOR; MANE, V.S. (Asian Journal of Chemistry, 2010)
A process for the production of the ethyl ester from Karanja oil to use as a biodiesel fuel has been studied. The essential part of the process is the transesterification of Karanja oil using methanol. NaOH is used as catalyst to yield methyl ester of Karanja oil as a product and glycerol as a by-product. Experiments have been performed to determine the optimum conditions for the preparation of ester. The process variables were temperature, catalyst, methanol used. Further the engine performance of biodiesel were checked with petroleum diesel and found almost identical.